Outcomes of School Resource Organizing Health Diagnostics - Triatna, Cepi; Herawan, Endang; Hartini, Nani; Rosalin, Elin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
School management is the most basic part of education management. The application of education management in school organizations is a nationally applicable education system component. This study aims to analyze how to detect school management diseases so that health or prevention efforts can be identified. The chosen research method is descriptive in the form of research and development. The research subjects were school principals, teachers, and administration. The school categories were selected from public and private junior high schools. The data collection instrument was developed as a questionnaire instrument to test the correctness and suitability of health indicators in the organization of school resources by practitioners in schools. Based on the results of the calculation of the Weight Mean Score (WMS) as a whole, the dimensions are included in the very healthy category with an average score of 3.42, and when converted on a scale of 1-100, the resulting score is 85.48. From these data, it can be concluded that Public and Private Junior High Schools are ready to organize school resources so that these school organizations can remain disease-free.